LSB-based Audio Steganography Method Based on Lifting Wavelet Transform - Pooyan, M.; Delforouzi, A. (2007 IEEE International Symposium on Signal Processing and Information Technology, 2007)
In this paper we present a novel method for digital audio steganography where encrypted covert data is embedded into the wavelet coefficients of host audio signal. To avoid extraction error we use lifting wavelet transform. For using the maximum capacity of audio signals, we calculate hearing threshold in wavelet domain. Then according to this threshold data bits are embedded in the least significant bits of lifting wavelet coefficients. Inverse lifting wavelet transform is applied to modified coefficients to construct stego signal in time domain. Experimental results show that proposed method has large payload, high audio quality and full recovery.